6ER-018 Development and performance evaluation of the medicines optimisation assessment tool: a prognostic model to target hospital pharmacists' input to prevent medication-related problems. (March 2019) - Geeson, C; Wei, L; Franklin, BD
Abstract : This poster was presented at the EAHP Congress, March 27–29, and is accepted for publication in the International Journal of Pharmacy Practice.